“Question of the Day”: Impact on learning and retention - Satheesha Nayak, B.; Mohandas Rao, K.G.; Sundarshan, S.; Naveen, K.; Srinivasa Rao, S.; Ashwini Aithal, P. (Kathmandu University Medical Journal, 2017)
See PDF for abstract